6p-3p+7p=

Simple and best practice solution for 6p-3p+7p= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p-3p+7p= equation:


Simplifying
6p + -3p + 7p = 0

Combine like terms: 6p + -3p = 3p
3p + 7p = 0

Combine like terms: 3p + 7p = 10p
10p = 0

Solving
10p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Divide each side by '10'.
p = 0.0

Simplifying
p = 0.0

See similar equations:

| 6(7x+7)=7(6x+1-6) | | -0.4(y+.75)=-0.6666(y+3) | | -7(m-7)+1=-16+4m | | Y=5+50*x | | 15+5d=8d | | 2a-6=4a-2 | | 0.3a+(2-0.5)+0.2(a+2)=1.3 | | X=2.2 | | x^2+6x-4=5 | | -8-y=y-4y | | 3x+39+2x+14=72 | | -3=-4v+5v | | 7x-5(2x+4)=16 | | -4y-2=-14 | | -1=4b+6-3b | | -2x^3+x^2+15x=0 | | 6y+7=2y+19 | | x-10=3+x/2 | | 14=9x+5+8 | | 11+x+5x=1+8x | | 2m-13=7m+27 | | 3x+39+1x+36=72 | | -v-3=3 | | 4(5y-3)-3y=5 | | 5+2.2h=-3.7 | | b+3(b)=64 | | -4m-4-8m=8-6m | | m(x)=5x-5 | | -4x+-36=-8 | | (x)=5x-5 | | 4(5y-3)-3=5 | | 8w-2=-10w-30+4 |

Equations solver categories